Biaya Relevan Untuk Peningkatan Laba UMKM Wilayah Cimahi, Jawa Barat - Leny Suzan; Muhamad Muslih (CV. Multi Kreasi Media, 2023)
Micro, small and MSE enterprises (MSEs) are one of the drivers of the Indonesian economy. One of the cities with a relatively high percentage of MSEs is Cimahi City in West Java. According to the Ministry of Cooperatives and SMEs, the number of SMEs reached around 99.8% in 2019, and the proportion of medium and large enterprises reached around 0.11%. The MSME sector also contributes significantly to employment, absorbing around 84% of the total Indonesian workforce. To improve the economy, the Cimahi City Government has implemented several programs that can improve the economy of the community, especially the people of Cimahi City. One of the obstacles faced by MSEs is the ability to compete in determining selling prices. Relevant costs are future costs that differ among alternatives and have a relationship with opportunity costs, where differential costs are various cost differences among a number of alternative choices that can be used by MSEs. Errors in conducting analysis result in higher production costs and reduce MSE profits. This condition can be understood because they only consider internal direct costs which are costs attached to products in MSEs only. With this condition, the community service team of the Faculty of Economics and Business of Telkom University hold activities aimed at MSEs in the Cimahi area, and focus on how to identify relevant activities and costs so as to increase calculation accuracy which will provide a competitive advantage in the form of increasing MSE profits.